Accuracy of computer-generated, Spanish-language medicine labels. - Sharif I; Tse J (Pediatrics, 2010)
OBJECTIVE: We evaluated the accuracy of translated, Spanish-language medicine labels among pharmacies in a borough with a large Spanish-speaking population. METHODS: A cross-sectional, telephone survey of all pharmacies in the Bronx, New York, was performed. Selected pharmacies were visited to learn about the computer software being used to generate Spanish medicine labels. Outcomes included the proportion of pharmacies providing Spanish medicine labels, frequency of computerized translation, and description of Spanish medicine labels produced. RESULTS: Of 316 pharmacies, 286 (91%) participated. Overall, 209 (73%) provided medicine labels in Spanish. Independent pharmacies were significantly more likely to provide Spanish labels than were hospital or chain pharmacies (88% vs 57% vs 32%; P < .0001). Pharmacies that provided Spanish labels mostly commonly (86%) used computer programs to do so; 11% used lay staff members, and 3% used a professional interpreter. We identified 14 different computer programs used to generate Spanish labels, with 70% of pharmacies using 1 of 3 major programs. We evaluated 76 medicine labels generated by 13 different computer programs. Overall, 32 Spanish labels (43%) included incomplete translations (a mixture of English and Spanish), and 6 additional labels contained misspellings or grammar errors, which resulted in an overall error rate of 50%. CONCLUSIONS: Although pharmacies were likely to provide medicine labels translated into Spanish, the quality of the translations was inconsistent and potentially hazardous. Unless regulations and funding support the technological advances needed to ensure the safety of such labeling, we risk perpetuating health disparities for populations with limited English proficiency.